Mycobacteria other than tubercle bacilli in sputum specimens from patients in Manaus (Amazonia, Brasil) - Salem, Júlia Ignês; Marója, Maria de Fatima; Carvalho, Francisco Martinho; Lima, Mari Otsuka de; Feuillet, Antoinette (Acta Amazonica, 1989)
Mycobacteria which are most commonly isolated in pulmonary secretions of patients with respiratory symptoms living in the State of Amazonas are given. The high percentage of isolates (25,4) and the species obtained indicate a strong relationship of contamination of man by the environment. Among the species isolated, seven of them are considered potentially pathogenic mycobacteria. Since some of these species may interfere with present and further vaccination programs against Tuberculosis and Leprosy, these investigations indicate a necessity of carrying out studies of population awareness against specific PPD's prepared from the same species.